Modeling for Sustainable Management in Agriculture, Food and the Environment 2021
DOI: 10.1201/9780429197529-3
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Land Use and Land Cover Changes in the Mediterranean Agricultural Ecosystems

Abstract: Land use and land cover (LULC) is a powerful driver of sustainable landscape development, conservation and management. This is especially true for Mediterranean agricultural landscapes, which are increasingly sensitive to human activities, water scarcity and climate change. Therefore, this study investigates the patterns, dynamics and driving forces of LULC changes affecting Mediterranean agricultural ecosystems, taking southern Spain (regions of Andalusia and Murcia) as a representative case study. Analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Nowadays, the location of croplands in Southern Europe does not depend so much on physical or biophysical factors, and there is an increasing tendency to locate farms in more degraded areas and with a low water capacity, a long way from cities and markets [45]. This was highlighted in a study in Spain by Bakker and Veldkamp [46], who found that factors such as topography, soil quality, and accessibility have become less important in the location of cropland, and crop cultivation is increasingly concentrated in warm and sunny areas where high production is ensured with the help of modern technology such as irrigation and land levelling, as is happening in the south and southeast of the Iberian Peninsula with the aid of greenhouse and drip irrigation techniques [47]. In the provinces we studied, we did not detect higher levels of abandonment around the cities as had been noted by Bakker et al [45]; in fact, in Soria, there has been an expansion in agriculture around the city, and nor did we notice lower levels of abandonment within the Natura 2000 network in relation to conservation policies for the maintenance of sustainable agriculture, as reported by Levers et al [2].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the location of croplands in Southern Europe does not depend so much on physical or biophysical factors, and there is an increasing tendency to locate farms in more degraded areas and with a low water capacity, a long way from cities and markets [45]. This was highlighted in a study in Spain by Bakker and Veldkamp [46], who found that factors such as topography, soil quality, and accessibility have become less important in the location of cropland, and crop cultivation is increasingly concentrated in warm and sunny areas where high production is ensured with the help of modern technology such as irrigation and land levelling, as is happening in the south and southeast of the Iberian Peninsula with the aid of greenhouse and drip irrigation techniques [47]. In the provinces we studied, we did not detect higher levels of abandonment around the cities as had been noted by Bakker et al [45]; in fact, in Soria, there has been an expansion in agriculture around the city, and nor did we notice lower levels of abandonment within the Natura 2000 network in relation to conservation policies for the maintenance of sustainable agriculture, as reported by Levers et al [2].…”
Section: Discussionmentioning
confidence: 99%